Tari Kreasi Bebarisan Bala Maya, Sebuah Kisah Prajurit Kupu-kupu - I Wayan Wira Arimbawa; I Kt. Suteja; Ni Nyoman Manik Suryani (UPT Pusat Penerbitan LP2MPP Institut Seni Indonesia Denpasar, 2022)
Reading a book Kupu Kupu Kuning Yang Terbang Di Selat Lombok, tell about history of struggle the kingdom of Karangasem defeating the Selaparang kingdom Lombok. The victory of the kingdom of Karangasem blessing from yellow butterfly troops which can be seen or invisible, panugrahan (Grace) from Ida Bhatara Alit Sakti at Pura Bukit Karangasem. The meaning of the struggle is very phenomenal, if it is related to the concept sekala and niskala, that is devotion of forefather and human relationship with universe. Oriented from the phenomenon came up with an idea to create a work creation dance with the title Bala Maya in bebarisan creation. In the creation of this dance, using theory image and imagination by Tetdjoworo,H, that is can imagining and manifest in the motive of movement.The process uses the method Mencipta Lewat Tari by Y.Sumadiyo Hadi translation of the book Creating Through Dance by Alma M.Hawkins consists of three step that is, exploration, improvisation, and forming step. Bala Maya is a bebarisan dance creation have a heroism theme, tell about Laskar Karangasem troops which interpreting the yellow butterfly attack Seleparang Lombok Kingdom. Invisible soldier is the character and characteristic of yellow butterfly called Bala Maya. Keywords : Bebarisan dance, Bala Maya, sekala-niskala, creating.